Review on Rain drop detection and removal using k-means clustering and Hough transformation - Kullarkar, SP; Jain, SV (International Journal of Computer Sciences and Engineering, 2025)
Raindrops stick to a window glass can considerably destroy the visibility of a scene. Detecting and removing raindrops will benefit in many computer image applications. We presented hybrid approach to detect and remove raindrops and then restore the image back ground in a single image. Proposed framework is based on K-means clustering and hybrid Otsu plus median filter for the efficient retrieval of Rain droplets from the single image. The k-means clustering is used which results in highest correct clustering rate and Hough transform is used to detect and remove the raindrops from single image. We present a complete review on different approach for raindrop detection and removal. The proposed system will gives better results than available approaches for raindrop detection and removal. Results analysis will be performed on the basis of the efficiency and accuracy of the proposed method.